2013
DOI: 10.1177/1069072712475164
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Social Status and Family Support to College Students’ Career Decision Self-Efficacy and Outcome Expectations

Abstract: The purpose of this study was to better understand the roles of social status and family support in the career decision making of young adults in college. We tested a path model predicting career decision self-efficacy and career-related outcome expectations in a sample of 270 male and female undergraduate students. Predictor variables included family of origin socioeconomic status, perceived social status, perceived family support, and intentional family career-related interactions. The sample was randomly sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 63 publications
(110 reference statements)
3
114
0
9
Order By: Relevance
“…A sample item from the instrument is "I have control over my career decisions." This instrument was tested with a sample of 270 undergraduate students from Pacific Northwest and the East Coast and had a Cronbach's alpha of .93 (Metheny & McWhirter, 2013). The alpha values for the present sample were α = .92 for pretest and α = .90 for posttest (see Table 8).…”
Section: Vocational Outcome Expectations -Revised (Voe-r; Mcwhirter Andmentioning
confidence: 89%
“…A sample item from the instrument is "I have control over my career decisions." This instrument was tested with a sample of 270 undergraduate students from Pacific Northwest and the East Coast and had a Cronbach's alpha of .93 (Metheny & McWhirter, 2013). The alpha values for the present sample were α = .92 for pretest and α = .90 for posttest (see Table 8).…”
Section: Vocational Outcome Expectations -Revised (Voe-r; Mcwhirter Andmentioning
confidence: 89%
“…Additionally, other family members and a parent or guardian were other agents that increased both belongingness to major and class. Metheney & McWhirter found that familial support for college increased the student's perceived social status, even for students (typically FGS) with low Social Economic Status (SES) 37 . Since college is a higher social status institution, family help fosters belongingness for all students, both CGS and FGS.…”
Section: Belongingnessmentioning
confidence: 99%
“…Zum einen kann dieser Status einen direkten Einfluss auf den Bildungserfolg haben, wenn beispielsweise eine bessere finanzielle Ausstattung die Anschaffung teurer Lernmaterialien ermöglicht (Metheny/McWhirter 2013). Dadurch kann die als erreichbar angesehene Statushöhe eines möglichen Berufes steigen.…”
Section: Interaktion Mit Dem Sozio-ökonomischen Status Der Elternunclassified
“…Die Beziehungs-und Strukturmerkmale wirken hierbei nicht losgelöst voneinander, sondern beeinflussen sich wechselseitig (Whiston/Keller 2004;Metheny/McWhirter 2013). Ein zentrales Strukturmerkmal der Familie ist der sozio-ökonomische Status des Berufs der Eltern, der mit dem angestrebten Status des Berufs der Kinder korreliert.…”
Section: Introductionunclassified
See 1 more Smart Citation